IGH Translocations in Chinese Patients With Chronic Lymphocytic Leukemia: Clinicopathologic Characteristics and Genetic Profile - Li, Qinlu; Xing, Shugang; Zhang, Heng; Mao, Xiao; Xiao, Min; Wang, Ying (Frontiers in Oncology, 2022)
Immunoglobulin heavy chain translocations (IGH-t) have occasionally been reported in Chinese patients with chronic lymphocytic leukemia (CLL). The objective of the present study was to identify the clinicopathologic features of patients with IGH-t CLL and compare them with those of patients with non-IGH-t CLL. We performed fluorescence in situ hybridization (FISH) based on a routine CLL prognostic FISH panel using IGH, IGH-BCL2, BCL3, IGH-CMYC, and BCL6 FISH probes. Furthermore, we retrospectively evaluated the clinical features of 138 newly diagnosed CLL patients via chromosome banding analysis (CBA), FISH, and targeted next-generation sequencing. IGH-t was identified in 25 patients (18.1%). Patients with IGH-t CLL had lower flow scores than those with non-IGH-t CLL. The most frequent translocation was t(14;18) (10 patients), followed by t(14;19) (3 patients), and t(2;14)(p13;q32), t(7;14)(q21.2;q12), t(9;14)(p13;q32) (3 patients). The remaining nine patients included three with abnormal karyotypes without translocation involving 14q32, four with a normal karyotype, and two who failed CBA. The most frequently concomitant FISH-detected aberrations were 13q deletion, followed by +12 and TP53 deletion, while one case involved ATM deletion. Complex karyotypes were detected in five patients with IGH-t CLL, in whom all partner genes were non-BCL2. Available mutational information indicated that KMT2D mutation was the most frequent mutation among tested 70 patients, while TP53 mutation was the most frequent mutation in the IGH-t group. Moreover, the IGH-t group had higher FBXW7 (P=0.014) and ATM (P=0.004) mutations than the non-IGH-t group, and this difference was statistically significant. Our study demonstrates that IGH-t is not uncommon among Chinese CLL patients, and that its partner genes are multiple. The gene mutational profile of the IGH-t group was distinct from that of the non-IGH-t group, and the concomitant chromosomal abnormalities within the IGH-t CLL group differed. Thus, identification of IGH-t and its partner genes in CLL patients may help further refine risk stratification and strengthen the accurate management in CLL patients.